Odontogenic Cervicofacial Infection in Pregnancy: A Need for Oral Care - Benjamin Fomete; Rowland Agbara; Kelvin Uchenna Omeje; Adekunle Olanrewaju Oguntayo (Tehran University of Medical Sciences, 2021)
Objective: During pregnancy, changes occur in the oral environment with gingivitis predominating. The development of odontogenic infections within the period of pregnancy may endanger the life of the mother as well as that of her unborn baby. Materials and methods: A retrospective observational study of cases of cervicofacial infection in women during pregnancy was conducted at the oral and maxillofacial surgery clinic of a northern Nigerian tertiary health care center from January 2006 to June 2018. Results: Seventy women were managed for cervicofacial infection during the period reviewed, out of which 20 women (28.6%) presented during pregnancy. Their mean age was 33.8 ± 9.35 years with a range of 20 to 55 years. The 30-39 years age bracket had the highest frequency (40%) and the mean duration of pregnancy at presentation was 24.9 ± 11.12 weeks with a range between 10 to 36 weeks. Majority (n=15, 75.0%) presented in the 3rd trimester. At presentation, the frequently involved fascial space was unilateral submandibular space (n=10; 50.0%), All the patients had incision/drainage/decompression on the dental chair under local anesthesia (2% lidocaine with 1:80,000 adrenaline). The mean length of hospital stay was 13.9 ± 6.2 days with a range of 6 to 26 days. The mortality rate was 15% (n=3 cases). Conclusion: There is a need for oral health evaluation in pregnant women during ante-natal visits to prevent these complications. Oral health education should also form part of teachings received by women both in the ante-natal and postnatal clinics.